Nikah Sirri dan Urgensi Pencatatan Perkawinan - Shofiyah, Shofiyah (MADINAH, 2014)
Marriage is the sunnah of Rasulullah SAW, which places the male relation as husband and woman as wife in strong and honorable bond (mitsaqon qalidho). This is a typical human celebration that distinguishes between the other creatures of God. Which in the human life of marriage events arranged in such a way through religion, customs and also the norms of other rules. Because in essence marriage is a complete agreement that is not only dimension of humanity but also dimension of the Godhead that the terms of the meaning set in the Qur'an and hadith as described and practiced by the Prophet Muhammad. Related to this marriage marriage sirri until now is still a trend among the people with a valid excuse according to the Islamic Shari'ah after the eligibility and marriage, but the marriage is seen from the standpoint of formal law has several sides weakness, therefore in Article 2 paragraph 2 Law No. 1 of 1974 as well as in Article 5 paragraph 1 and 2 compilation of Islamic marriage law shall be recorded by authorized officers to obtain legal legal power, therefore the registration of marriage becomes very urgent.